Screening and Identification of Erythrocyte Antibodies: A Narrative Literature Review - Yashinta Octavian Gita Setyanda; Rofinda, Zelly Dia (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Red blood cell (RBC) alloimmunization, the development of antibodies against foreign red blood cell antigens, is a critical concern in transfusion medicine. Alloantibodies can lead to adverse transfusion reactions, including hemolytic disease of the fetus and newborn (HDFN) and delayed hemolytic transfusion reactions (DHTR). This comprehensive literature review explores the intricacies of RBC alloimmunization, focusing on the screening and identification of erythrocyte antibodies. We delve into the prevalence and clinical significance of various alloantibodies, the underlying immunological mechanisms, and the evolution of laboratory techniques for their detection. Additionally, we discuss the challenges and future directions in managing alloimmunization, emphasizing the importance of personalized medicine and innovative approaches to ensure safe and effective blood transfusions.